Use of isolated populations: pitfalls and potential - Peltonen, Leena (Henry Stewart Talks, 2007)
Disease mutations in Finland, Molecular background of Finnish disease heritage, Finnish disease genes, novel pathways exposed, Example: APECED, AIRE protein, AIRE regulates ectopic expression in thymus, AIRE deficiency, Simplifying the complex genetic background of common diseases, Advantages of isolated populations, Internal isolates: increased genetic homogeneity, Lactose intolerance, Adult type hypolactasia, Severe coronary heart disease, Familial combined hyperlipidemia, FCHL, USF1: a transcription factor, Effect of genetic association on target cells, coronary wall and impact in population, Population based cohorts in Finland, Global effort is needed
Archived at 2021/02/25